(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
There is Demand-Supply gap in organs needed for transplantation worldwide mainly because of availability of safe and accessible transplantation surgeries for broader population. Various nations of the world have tried to fulfil demand-supply gap with transplantation friendly legislations along with more investment in development of transplantation facilities. Review about practise of consent and related issues in relation to organ donation of various country will give better understanding about global prospective of these issue. One of the debatable issues related to change in legislation is about type of consent for cadaver organ retrieval. Most of the countries in world are following model of ‘expressed consent’ for deceased organ transplantation but some countries following model of ‘presumed consent, with encouraging result in form of higher organs donation rate. Third model of consent is ‘Tacit consent’ (which have many similarity with implied consent model) is also being followed in few countries. Capability of donor to give consent for directed donation to the particular person or group is also getting importance for cadaver donation. Both non-financial and financial Incentive from government to get consent for organ donation is also being practised differently in countries of the world. Role of family members and importance of their consent before